2010
DOI: 10.1111/j.1439-0396.2008.00898.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term feeding effects of dietary protein levels on egg production, immunocompetence and plasma amino acids of laying hens in subtropical condition

Abstract: The objective of this study was to determine the effect of protein levels on production performance, immune response, liver triglyceride and plasma amino acids profile of laying hens during 21-48 weeks of age. Two groups of commercial hens (Babcock B-308) were fed with diets with different crude protein levels (14% and 18% CP). The high protein diet (18% CP) significantly increased production performance, essential amino acid intake, spleen weight (% of body weight), ND-titre (haemagglutination-inhibition test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 57 publications
6
14
0
Order By: Relevance
“…A similar change in plasma glycoalbumin concentration was observed in chickens fed the CP 0% diet, whereas plasma albumin concentration was decreased by protein-deprivation (Table 3). It is well-known that plasma levels of chicken albumin are easily affected by changes in dietary CP levels (Takahashi et al, 1995;Poosuwan et al, 2010), which is in agreement with the results derived in the present study. In addition, as there was no change in plasma glucose concentrations from feeding a protein-free diet, the increase in the ratio of glycoalbumin to albumin might be due to both an increase in plasma glycoalbumin and a decrease in plasma albumin by feeding the CP 0% diet.…”
Section: Discussionsupporting
confidence: 83%
“…A similar change in plasma glycoalbumin concentration was observed in chickens fed the CP 0% diet, whereas plasma albumin concentration was decreased by protein-deprivation (Table 3). It is well-known that plasma levels of chicken albumin are easily affected by changes in dietary CP levels (Takahashi et al, 1995;Poosuwan et al, 2010), which is in agreement with the results derived in the present study. In addition, as there was no change in plasma glucose concentrations from feeding a protein-free diet, the increase in the ratio of glycoalbumin to albumin might be due to both an increase in plasma glycoalbumin and a decrease in plasma albumin by feeding the CP 0% diet.…”
Section: Discussionsupporting
confidence: 83%
“…A relatively short time of feeding laying hens (12 weeks) and a small difference in protein contents (14, 16 and 18%) have been shown to cause a significant difference in ND titres between those fed diets containing 14 or 16% protein (2.2 and 2.5 antibody titres, respectively) and those fed a diet containing 18% protein (4.2) [ 26 ]. A similar result was also found at 27 weeks in laying hens fed a 14% CP diet (2.0) compared with those fed an 18% CP diet (3.3) [ 29 ]. It is not possible to identify the specific cause of the reduced antibody titres in the pigeons on the 6 and 10% CP diets, but a reduction in the ability of B-lymphocytes to synthesize antibodies due to reduced availability of amino acids or an imbalance in amino acids [ 52 ] could have contributed; it is also possible that receptors on cell surfaces of other types of lymphocyte involved in antigen recognition or production of cytokines were reduced [ 21 , 52 ].…”
Section: Discussionsupporting
confidence: 72%
“…[30] In addition, sufficient methionine levels in the diet have been demonstrated to be necessary for sustaining normal immunocompetence and achieving maximum egg production in laying hens in subtropical conditions. [31] Bunchasak and Silapasorn [32] reported that laying hens under tropical conditions fed a low-protein diet (14% crude protein) supplemented with 0.44% methionine improved egg production and egg weight. In the same study bird mortality was reduced, and egg shell thickness was improved when these hens were supported with methionine in feed.…”
Section: Resultsmentioning
confidence: 99%